Qualitative research in organizations and management an international journal. ([Bradford, West Yorkshire, England] Emerald Group Publishing Limited, 2006)
Qualitative Research in Organizations and Management is an international journal committed to encouraging and publishing qualitative work from researchers and practitioners within the management and organizational field throughout the world. The journal seeks to provide a forum for qualitative researchers through which they can share their work with others and discuss issues of research practice of particular pertinence to qualitative approaches.
UP System perpetual contents: 2021-2023
Keywords: Industrial management -- Research -- Periodicals; Business enterprises -- Research -- Periodicals; Qualitative research -- Periodicals